Protein profilong of chicken breast muscle from different slaughter houses in relation to meat quality - Md Zin, Noor Hasniza; Abdul Halim, Murni; Muhamad Bunnori, Noraslinda; Haron, Normah; Abdul Wahab, Widya (2016)
Chicken meat is a source of protein in human diet. Protein content and values defines the quality of the chicken meat. This research aimed to analysed variations of protein profiles in chicken breast muscles from different slaughtering houses by using proteomic strategies.